THE POLITICAL SOCIOLOGY OF ÉMILE DURKHEIM: THE CENTRALITA OF THE PROBLEM OF THE STATE IN HIS REFLECTIONS FROM THE YEARS 1883-1885 (Andamios, Revista de Investigación Social, 2008)
The sociology of Durkheim is not limited to his best-known and most analyzed works. There are writings (critiques, articles, essays, speeches, lessons) that are less famous, only recently distributed worldwide and not yet translated into Spanish, that contain Durkheim’s theoretical reflections and participation in the political debates of latenineteenth century and early twentieth century France. These writings serve to enrich our comprehension of his creative output. Among these writings are those that belong to the period 1883-1885, shortly before the presentation of his major work The Division of Labor in Society, and which constitute the raw material of this investigation.
Keywords: Durkheim; Classic; Political Sociology; State; 1883-1885